COMPARATIVE STUDY ON THERAPEUTIC EFFICACY OF MINOXIDIL AND PLATELET-RICH PLASMA EXOSOME IN ANDROGENETIC ALOPECIA MICE MODELS - MULIANTO, NURRACHMAT; JULIANTO, INDAH; IRAWANTO, MUHAMMAD EKO; DHARMAWAN, NUGROHOAJI; MONICA, PRISTIA WIDYA; OKTAVIANI, TRYA (International Journal of Applied Pharmaceutics, 2025)
Objective: Androgenetic alopecia (AGA) is a common type of hair loss worldwide. Currently, available treatment options for AGA show inconsistent results and may cause various undesirable side effects. Platelet-rich plasma exosomes (PRP-Exo) is one of the therapeutic modalities that has shown satisfactory results to treat hair loss. This study aims to assess the effectiveness of minoxidil and PRP-Exo for AGA. Methods: An experimental investigation was conducted using alopecia BALB/c mice to examine hair follicle characteristics. Fourteen mice were divided into two groups, one group received daily topical application of 5% minoxidil, meanwhile, the other group received 0.1 ml injections of PRP-Exo on days 11, 18 and 25. Follicle density and the anagen: telogen ratio were evaluated histopathological. Results: The administration of PRP-Exo resulted in significantly different follicle density (68.61±7.64 vs. 40.14±11.60; p = 0.007) and anagen: telogen ratio (0.34±0.04 vs. 0.22±0.02; p = 0.009) compared to minoxidil. Conclusion: This investigation demonstrates that PRP-Exo effectively enhance both hair follicle density and the anagen: telogen ratio in the AGA mice model when compared to minoxidil 5%.